2015
DOI: 10.1097/jcp.0000000000000314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Doses of Prosocial Drugs Methamphetamine and Alcohol on Plasma Oxytocin Levels

Abstract: Many drugs, including alcohol and stimulants, demonstrably increase sociability and verbal interaction and are recreationally consumed in social settings. One drug, 3,4-methylenedioxymethamphetamine (MDMA, “ecstasy”), appears to produce its prosocial effects by increasing plasma oxytocin levels, and the oxytocin system has been implicated in responses to several other drugs of abuse. Here, we sought to investigate the effects of two other “social” drugs on plasma oxytocin levels: methamphetamine and alcohol. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 28 publications
3
27
2
3
Order By: Relevance
“…While the effects of acute METH administration on the central OTR system and plasma oxytocin levels are yet to be determined, it is unlikely that the observed upregulation of amygdalar OTR and plasma OT levels to reflect the acute effects of the drug since Sarnyai et al, 1992 has previously reported no effects of acute cocaine (another psychostimulant drug) on oxytocin content in plasma and amygdala. In support, acute doses of methamphetamine did not alter plasma OT levels in healthy adults (Bershad et al, 2015). In contrast to the normalized levels of plasma OT and amygdalar OTR binding following methamphetamine abstinence,…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 64%
“…While the effects of acute METH administration on the central OTR system and plasma oxytocin levels are yet to be determined, it is unlikely that the observed upregulation of amygdalar OTR and plasma OT levels to reflect the acute effects of the drug since Sarnyai et al, 1992 has previously reported no effects of acute cocaine (another psychostimulant drug) on oxytocin content in plasma and amygdala. In support, acute doses of methamphetamine did not alter plasma OT levels in healthy adults (Bershad et al, 2015). In contrast to the normalized levels of plasma OT and amygdalar OTR binding following methamphetamine abstinence,…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 64%
“…As expected (Bershad et al 2015), alcoholic beer produced positive subjective effects, including stimulation and happy and prosocial effects, such as increases in being talkative and open and the desire to be with others and not alone. These subjective effects likely contribute to the prosocial effects of alcohol.…”
Section: Discussionmentioning
confidence: 80%
“…A possible mediator is oxytocin, which is a key regulator of emotional and social behaviors (Heinrichs et al 2009). Although evidence suggests that chronic alcohol administration affects oxytocinergic function in the brain (Silva et al 2002), only two very small studies tested the acute effects of alcohol on circulating oxytocin (Bershad et al 2015;Mennella and Pepino 2006) and the findings were inconclusive. Oxytocin has been shown to facilitate the recognition of positive facial expressions (Di Simplicio et al 2009;Marsh et al 2010) and enhance emotional empathy (Hurlemann et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations